Analysis of Celebrity Worship Behavior in the Lifestyle of K-POP Fans in the Seventeen Fandom in Yogyakarta - Juwita, Rahmania; Nurnisya, Frizki Yulianti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The phenomenon of Korean wave globalization is spreading South Korean culture worldwide. One of them is Indonesia, which entered through the broadcast of Korean dramas to attract attention from visuals, storylines, and interesting accompanying music called K-pop. Having great enthusiasm for K-pop gave rise to a group of fans of the K-pop boy band SEVENTEEN called CARAT. In providing support to SEVENTEEN, CARAT provides support by buying merchandise. K-pop fans' behavior shows their obsession or adoration towards their idols, often called celebrity worship. This type of research is qualitative research with phenomenological methods and an interpretive paradigm approach. Data collection techniques use interviews, documentation, and observation and analyze data through four activities: data collection, data reduction, data display, verification, and conclusion making. The results of this study indicate that the formation of celebrity worship behavior in fans refers to each component stage in celebrity worship, namely Entertainment-social, Intense-personal, and Borderline-pathological, with fantasy behavior that is not excessive. SEVENTEEN fans experience changes in lifestyle by paying more attention to personal appearance, changing mindsets, and strengthening social relationships.